The surplus value of Azorean Camellia sinensis flowers as an important contributor affecting the nutraceutical benefits of green tea quality - Baptista, José (2022)
Leaves from Camellia sinensis have been used to make teas for a long time, however, less attention has been paid to the flowers, which is a waste of an abundant resource that should be valorized. This study evaluates the representative tea metabolites content (dry weight basis) and antioxidant properties of Azorean C. sinensis flowers as compared to commercial Gorreana green tea (GorGT), the only one produced in Europe. We determined the variability of catechins, caffeine and L-theanine (THEA) by RP-HPLC/DAD and the confirmation of THEA by GC/MS. The antioxidants activities were determined by FRSA, FRAP and FIC methods. The total phenolics and total flavonoids were determined by the Folin-Ciocalteu and colorimetric methodologies. The results showed that flowers presented higher L-theanine (5.88 mg/g) but lower caffeine (4.10 mg/g) contents than GorGT (2.59 and 12.42 mg/g, respectively) and, therefore, a lower caffeine/theanine ratio (0.70 versus 4.80). The esterified catechins content (in percentage of total catechins) showed similar values for flowers (85.34%) and GorGT (86.45%), and the individual catechins decreased as follows: epigallocatechin-3-gallate > epicatechin-3-gallate ≫ gallocatecin-3-gallate. In antioxidant assays, GorGT presented better FRSA and FRAP but similar FIC as compared to flowers. Also, the total phenolics and flavonoids contents of dried extract presented higher values in GorGT: 321.56 mg gallic acid equivalents (GAE)/g and 47.17 mg rutin equivalents (RE)/g as compared to 141.94 mg GAE/g and 24.14 mg RE/g, respectively, for flowers. This study represents the first contribute to Azorean C. sinensis flowers valorization as a new-added material with nutraceutical benefits.